A concept note on co-creating a living lab for locally led climate adaptation: Integrating local public procurement into Brazil's climate plan - Nehring, Ryan; Farraz, Gabriel; Curan, Roberta; Magalhaes, Marilia; Benfica, Rui; Schneider, Sergio; Tângari, Juliana (CGIAR System Organization, 2025)
Effective climate action depends not only on national commitments, but on the capacity of subnational governments to operationalize them. In Brazil, this challenge is particularly salient due to the country's size, socio-biodiversity, and decentralized model of public service delivery.